Bidirectional relationship between L2 pragmatic development and learner identity in a study abroad context. (July 2022) - Liu, Xiaowen; Lamb, Martin; Chambers, Gary N.
Abstract: In recent years, the connection between learner identity and learning of L2 pragmatics has received more attention in applied linguistic research. Nevertheless, investigations on this topic have mainly focused on the role of learners' identity in their L2 pragmatic choices. The reverse influence has not been adequately investigated in empirical studies – how learning of L2 pragmatics could potentially foster learners' identity change. This article aims to expand our understanding of the link between identity and L2 pragmatic development in the study abroad context by describing a longitudinal case study which tracked the experiences of four Chinese postgraduate students sojourning in the UK. Data were generated through interviews and online chat over a 12-month period. Findings indicate a bidirectional influence between L2 pragmatics development and learners' sense of self: learners' pragmatic judgements and preferences are influenced by identity-related factors, such as internalised cultural values and their perceived foreigner and ELF identities; in return, exposure to new L2 pragmatic features can prompt learner reflection on interpersonal relationships and self-positioning, which may then lead to identity development. Highlights: SA students tend to interpret new pragmatic features in the light of existing cultural and language knowledge. Even students with solid motivation to learn British English sometimes reject NS pragmatic norms due to identity-related considerations. Metapragmatic analysis can trigger SA students to reflect on and even reshape their sense of self. Exploring sociocultural meanings behind linguistic forms, some SA students develop intercultural awareness.